The potential of the ora-pro-nóbis (Pereskia aculeata Mill.) in the National School Feeding Program (Research, Society and Development, 2021)
The acquisition of diversified and local food with a focus on sustainable rural development is among the guidelines of the National School Feeding Program. Of wide culinary application, high adaptability and low production cost, the ora-pro-nóbis (Pereskia aculeata Mill.) is a Brazilian native non-conventional food plant with high content of essential amino acids, fibers, iron and carotenoides, considered an alternative to improve nutritional quality, enhance biodiversity and encourage local family farming. The exploratory study aims to analyze the potential of this representative of Brazilian biodiversity from an action Food and Nutrition Education to students from 8 to 10 years of a school of Captain Leonidas Marques – PR. A semi-structured questionnaire was used to evaluate the acceptability of the ora-pro-nóbis (Pereskia aculeata Mill.) in the diet and knowledge about unconventional food plants. The action involved four pre-established revenues with the use of this plan and the return of the students regarding the proposed practice, indicated good acceptance of the preparations. Nature is all around us, it is up to us to perceify it and give its due value, with this, this study opens doors to the world of underutilized and traditional species with food potential available in biodiversity. Themes like this contribute to the disruption of food monotony, transformation of food systems and promotion of food and nutrition security of the population.